Internet Use for Creative Purposes and Its Correlation with Perceived Usefulness, Computer Anxiety, and Emotional Intelligence: The Intermediary Effect of the Perceived Ease of Use - Kurtuluş Demirkol; Sena Esin İmamoğlu; Şaziye Serda Kayman; Salih Zeki İmamoğlu; Serhat Erat (Behavioral Sciences)
Although researchers have shown great interest in the antecedents and consequences of internet use due to the internet becoming a part of daily life, there is a gap in the literature regarding the factors that affect teachers’ use of the internet for creative purposes. This study aims to empirically examine teachers’ use of the internet for creative purposes and explores its relationship with emotional intelligence, computer anxiety, and the perceived ease of use of the internet. Furthermore, the possible intermediary effect of the perceived ease of use of the internet on creativity among these variables is also empirically investigated. In this context, data were obtained from 264 teachers in the Marmara Region in Turkey using a survey method. To test hypothesized relationships, structural equation modeling was conducted. Findings revealed that computer anxiety has a negative effect on creativity, while perceived usefulness, emotional intelligence, and the perceived ease of use have a positive effect. Our results also supported the partial mediating role of the perceived ease of use in the relationships between emotional intelligence and creativity, as well as between perceived usefulness and creativity, and the full mediating role of the perceived ease of use in the relationship between computer anxiety and creativity. Therefore, this research extends teachers’ understanding of technology acceptance and creativity by linking the two. Moreover, research findings provide important information to shape educational policies or professional development programs on the basis of digital education and offer a different approach to educators.